2022
DOI: 10.4018/ijdst.313053
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management Capability, Organizational Resilience, and the Growth of SMEs

Abstract: How small and medium-sized enterprises (SMEs) survive and grow is a matter of great concern not just to enterprises but also to governments. Although past studies have mainly focused on the driving forces of corporate growth, they have yet to investigate how SMEs can build resilience and then achieve growth through their own knowledge management within challenging environments. Therefore, this paper empirically examines the internal links among knowledge management capabilities (KMC), organizational resilience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Organizational resilience is defined as an important ability to identify, analyze and adapt to the dynamic environment in adversity. Its importance lies not in the capture of the market, but in the use of existing knowledge, technology and manpower to resolve the crisis in the face of emergencies and recession [6] Taking into account the price sensitivity, quantity driven and meagre profits of emerging markets, there may be some correlation or intrinsic role between organizational resilience and frugal innovation [17]. Organizational resilience mainly includes two dimensions, namely result-oriented ability and processoriented ability.…”
Section: Organizational Resilience and Frugal Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational resilience is defined as an important ability to identify, analyze and adapt to the dynamic environment in adversity. Its importance lies not in the capture of the market, but in the use of existing knowledge, technology and manpower to resolve the crisis in the face of emergencies and recession [6] Taking into account the price sensitivity, quantity driven and meagre profits of emerging markets, there may be some correlation or intrinsic role between organizational resilience and frugal innovation [17]. Organizational resilience mainly includes two dimensions, namely result-oriented ability and processoriented ability.…”
Section: Organizational Resilience and Frugal Innovationmentioning
confidence: 99%
“…That is, provide enterprises with more superior conditions to promote frugal innovation [5]. Digital transformation can help enterprises to enhance organizational resilience, enhance the stability and flexibility of enterprises, and drive the innovation of production process, business process and development strategy by reducing cost and increasing efficiency, optimizing allocation and improving the mode of information transmission [6]. Previous studies have found that design thinking is helpful to improve the thinking ability of low-cost design, exploring solutions and not sticking to traditional innovation in the process of frugal innovation, and helps to occupy and meet the requirements of emerging markets for high performance price ratio, simple design and concise products [7].…”
Section: Introductionmentioning
confidence: 99%